Arming Mesenchymal Stromal/Stem Cells Against Cancer: Has the Time Come? - Golinelli, Giulia; Mastrolia, Ilenia; Aramini, Beatrice; Masciale, Valentina; Pinelli, Massimo; Pacchioni, Lucrezia; Casari, Giulia; Dall’Ora, Massimiliano; Soares, Milena Botelho Pereira; Damasceno, Patrícia Kauanna Fonseca; Silva, Daniela Nascimento; Dominici, Massimo; et al. (Frontiers in Pharmacology, 2020)
Since mesenchymal stromal/stem cells (MSCs) were discovered, researchers have been drawn to study their peculiar biological features, including their immune privileged status and their capacity to selectively migrate into inflammatory areas, including tumors. These properties make MSCs promising cellular vehicles for the delivery of therapeutic molecules in the clinical setting. In recent decades, the engineering of MSCs into biological vehicles carrying anticancer compounds has been achieved in different ways, including the loading of MSCs with chemotherapeutics or drug functionalized nanoparticles (NPs), genetic modifications to force the production of anticancer proteins, and the use of oncolytic viruses. Recently, it has been demonstrated that wild-type and engineered MSCs can release extracellular vesicles (EVs) that contain therapeutic agents. Despite the enthusiasm for MSCs as cyto-pharmaceutical agents, many challenges, including controlling the fate of MSCs after administration, must still be considered. Preclinical results demonstrated that MSCs accumulate in lung, liver, and spleen, which could prevent their engraftment into tumor sites. For this reason, physical, chemical, and biological methods have been implemented to increase MSC concentration in the target tumors. Currently, there are more than 900 registered clinical trials using MSCs. Only a small fraction of these are investigating MSC-based therapies for cancer, but the number of these clinical trials is expected to increase as technology and our understanding of MSCs improve. This review will summarize MSC-based antitumor therapies to generate an increasing awareness of their potential and limits to accelerate their clinical translation.